WORKPLACE CONFLICT MANAGEMENT AND EMPLOYEE RETENTION: AN EMPIRICAL STUDY OF COCA-COLA NIGERIA LTD - Samson Odebode, Adebayo; Adeyinka Kayode, Comfort; Olalekan Dahunsi, Fatai; Celinah Timi-Eweje, Aanu; Oyinkansola Oderinwale, Oluwadara; Oyelakan Ayantunji, Isola (African Journal of Social and Behavioural Sciences, 2026)
Studies on conflict management strategies have gained greater attention in recent times and have been shown to be a key factor in retaining employees. The study investigated conflict management strategies and employees’ retention in Coca-Cola Nigeria Ltd. The specific objectives were to determine the influence of collaboration strategy on employees’ retention and to examine the influence of confrontation strategy on employees’ retention. The descriptive survey research design was adopted for the study. A total population of five hundred and eighty-one (581) serves the study population. Two hundred and thirty-seven (237) respondents were selected using Taro Yamane's formula for sample size determination; the study employed a simple random sample technique, data were collected using a structured questionnaire, and were analysed using descriptive and inferential statistics. Linear regression analysis was employed to test the stated hypotheses. All the research hypotheses were tested at a 0.05 alpha level. The findings of the study revealed that collaboration strategy significantly influenced employee retention (F(1,226) = 74.150, p < .000), and that confrontation strategy significantly influenced employee retention (F(1,226) = 177.385, p < .000). It was concluded that there was a significant and positive influence of conflict management strategies on employees’ retention in Coca-Cola Nigeria Ltd. The study therefore recommends that the organisation should take into consideration conflict resolution strategies because it has a significant influence on employees’ retention